Геральдичні традиції міст Лівобережної та Слобідської України (за матеріалами топографічних описів останньої чверті XVIII ст.) - Петрова, І. (Схід, 2010)
У статті аналізуються інформаційні можливості топографічних описів щодо формування геральдичних традицій міст Лівобережної та Слобідської України, визначено репрезентативність та достовірність описової інформації. Автором розглянуто процес поширення магдебурзького права на міста Лівобережної України за часів правління польських королів. Досліджено процес затвердження гербів за часів правління Катерини ІІ. The informative possibilities of topographical descriptions in relation to forming of heraldic traditions of cities of Livoberezwnaya and Slobodskaya Ukraine are analysed, representation and authenticity of descriptive information is defined in the article. The process of distribution of magdebur's right on the cities of Livoberezwnaya Ukraine in the days of the rule of Polish kings is considered by the author. The process of the claim of the coats of arms in the days of the rule of Kateryna II is examined.